The Last Blood of Unduk Ngadau: Development of 2D Animation in Cultural and Heritage Appreciation for UTHM Sarawakian Student - Imran Iskandar Mohd Salman; Yu Shi Min; Ai Risa Rachel Robern; Yahya, Mokhtar (Multidisciplinary Applied Research and Innovation, 2025)
Unduk Ngadau is a cultural beauty pageant in Sabah, Malaysia, open to all Sabahan women. The term means "Harvest Queen" in the Kadazan-Dusun language. It celebrates the grace, talent, and intellect of young women. The festival honors Hominodun, a symbol of fertility and abundance. She sacrificed herself during a famine to save her people, ensuring their survival by enabling crops to grow. The Kaamatan Festival commemorates her sacrifice and the bountiful harvest. Despite the rich cultural heritage and diverse folklore of Borneo, there is a growing concern over the preservation and promotion of these cultural assets in the modern era. Many of the traditional stories, languages, and customs of Borneo are at risk of being forgotten or overlooked, especially among younger generations and international audiences. Additionally, there is a need to create engaging and educational content that can serve as a cultural ambassador for Borneo, attracting tourists and visitors interested in experiencing the region’s unique heritage. The project aims to develop a 2D animation that introduces and promotes Borneo’s cultural heritage, focusing on its folklores and folktales. This animation will not only entertain but also the appreciation level among the Borneon students in UTHM. The methodology includes conducting interviews, administering surveys, researching online, and utilizing secondary data sources such as journal articles and internal records. The objective is to gain a comprehensive understanding of the issue and promote positive development in the issue while raising preserve and promote the cultural heritage of Borneo. The study of "The Last Blood of Unduk Ngadau" involves creating a cultural animation and evaluating its reception among Borneon students at UTHM. This research supports cultural preservation and education by accurately depicting cultural heritage in animation and assessing its impact.The animation reflects the traditions and history of indigenous communities, helping viewers understand and appreciate these cultures.